Efficient functionalization of oxide-free silicon(111) surfaces thiol-yne versus thiol-ene click chemistry - Bhairamadgi, Nagendra S (Langmuir : the ACS journal of surfaces and colloids, 2013)
Thiol-yne click (TYC) chemistry was utilized as a copper-free click reaction for the modification of alkyne-terminated monolayers on oxide-free Si(111) surfaces, and the results were compared with the analogous thiol-ene click (TEC) chemistry. A wide range of thiols such as 9-fluorenylmethoxy-carbonyl cysteine, thio-β-d-glucose tetraacetate, thioacetic acid, thioglycerol, thioglycolic acid, and 1H,1H,2H,2H-perfluorodecanethiol was immobilized using TYC under photochemical conditions, and all modified surfaces were characterized by static water contact angle measurements, X-ray photoelectron spectroscopy (including a simulation thereof by density functional calculations), and infrared absorption reflection spectroscopy. Surface-bound TYC proceeds with an efficiency of up to 1.5 thiols per alkyne group. This high surface coverage proceeds without oxidizing the Si surface. TYC yielded consistently higher surface coverages than TEC, due to double addition of thiols to alkyne-terminated monolayers. This also allows for the sequential and highly efficient attachment of two different thiols onto an alkyne-terminated monolayer